The grammatical category of gender in noun phrases of the Lithuanian-French interlanguage - Kazlauskienė, Vitalija (Taikomoji kalbotyra, 2017)
It is not an easy task for a Lithuanian, who is not a native speaker of French, to learn French nouns with their inherent grammatical gender, which is expressed by suffixes and articles non-existent in L1. The understanding of the category of gender of French L2 noun phrases is a complex and time consuming process. The data of the text corpus proves that students whose French language level is B1 have not fully comprehended the grammatical category of gender on all levels of linguistic competence.As demonstrated by the results of the present investigation, a student often does not assign a fixed gender. When in doubt, he/she eventually decides on the masculine gender as a universal choice, which in French is less codified than the feminine gender and is interpreted as the main gender from which other forms such as the feminine gender and the plural form are derived. Apparently, the cause of such confusion lies in the system of the French language itself. Students tend to assign the gender of the noun by semantic analogy, the analogy of form or meaning with the students’ first language or from a well-known word in L2; sometimes other languages such as English come into play. As regards the coordination of determiners and adjectives, the determiner coordination tends to cause fewer problems than adjectives. The latter is mostly used in the masculine form, regardless of the noun gender. Despite a number of nominal gender-related problems, a substantial number of nouns have been assigned the correct gender, as demonstrated by collocates agreeing in gender with respective nouns.
Keywords: noun-phrase; grammatical category of gender; corpus of Lithuanians learners of French